2012
DOI: 10.1007/s11356-012-0993-y
|View full text |Cite
|
Sign up to set email alerts
|

Energy reserves and accumulation of metals in the ground beetle Pterostichus oblongopunctatus from two metal-polluted gradients

Abstract: Living in an area chronically polluted with metals is usually associated with changes in the energy distribution in organisms due to increased energy expenses associated with detoxification and excretion processes. These expenses may be reflected in the available energy resources, such as lipids, carbohydrates, and proteins. In this context, the energy status of Pterostichus oblongopunctatus (Coleoptera: Carabidae) was studied in two metal pollution gradients near Olkusz and Miateczko Śląskie in southern Polan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 42 publications
2
13
0
Order By: Relevance
“…Our findings corroborate that food preferences, breeding and sex cause differences between toxic element concentrations in ground beetle species. Similar to other findings (Bednarska et al, 2013;Sklaski et al, 2011) we did not find significant differences in the toxic element concentrations in ground beetles along the urbanization gradient. Elements (Zn, Cu and Mn) are accumulated in the body in a relatively constant amount (Purchart and Kula, 2007).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our findings corroborate that food preferences, breeding and sex cause differences between toxic element concentrations in ground beetle species. Similar to other findings (Bednarska et al, 2013;Sklaski et al, 2011) we did not find significant differences in the toxic element concentrations in ground beetles along the urbanization gradient. Elements (Zn, Cu and Mn) are accumulated in the body in a relatively constant amount (Purchart and Kula, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…Thus, the differences between the toxic element concentrations of species may be caused by the different food preferences and different breeding. Bednarska et al (2013) demonstrated that species can use different strategies to survive in contaminated areas. Among carabid species, for example the P. oblongopunctatus are able to survive in pollutes areas, without any serious impact on their energy reserves (Bednarska et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations